Clinical Features and Surgical Outcomes of Spinal Tumors: A Multicenter Study - Syed Nasir Shah, Naeem Ul Haq, Muhammad Idris Khan, Zahid Khan, Walayat Shah, Main Ifthakar Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to evaluate the appearance, improvement, and complication rates of surgically removed spinal tumors. Material and Methods: After obtaining the ethics committee’s approval, this multicenter study continued from Jan 2020 to Jan 2021 at the Department of Neurosurgery mmc Mardan. This research covered all instances of spinal tumors that were surgically removed during this time. Recurrent spinal tumors and metastatic spinal cancers admitted for conservative or palliative care were excluded from this investigation. A neurological state comparison at six months with preoperative status is recorded. Version 26 of Spss software is used to evaluate data. Results: 27 female and 20 male patients totaling 47, were operated on during this time. In our research, intradural extra medullary lesions, which affected 18 patients (38.29%) the most, were followed by epidural lesions, which involved 13 patients (27.65%). Nine patients (19.14%) had an intradural intramedullary lesion. Pain in the form of backache, radiculopathy, and radiculomyelopathy (30 patients, 63.8%) is the most typical manifestation of these malignancies. The second joint Presentation is a motor impairment shown as a weakness (27 cases, 58.51%). CSF leak occurs in 05 individuals, with the most common postoperative consequence (7.44%). 75.5% of patients get good from a decent symptom result (36). There is evidence of neurological dysfunction in 3 cases (5.31%). Conclusion: The preferred course of therapy for spinal tumors is microsurgical excision with acceptable morbidity and successful surgical findings. Keywords: Spinal tumors, Microsurgical treatment,